Multipoint Kras oncogene mutations potentially indicate mucinous carcinoma on the entire spectrum of mucinous ovarian neoplasms - Lee, Yi-Ju; Lee, Ming-Yung; Ruan, Alexandra; Chen, Chi-Kuan; Liu, Hao-Ping; Wang, Chau-Jong; Chao, Wan-Ru; Han, Chih-Ping (Oncotarget, 2016)
Kras mutation is a common phenomenon in many human neoplasms. We aimed to assess the Kras mutational status along the histological continuum from normal ovaries to the development of benign, borderline and malignant ovarian mucinous neoplasms. We analyzed 41 cases of malignant, 10 cases of borderline, 7 cases of benign mucinous ovarian tumors and 7 cases of normal ovarian tissue. The prevalence of Kras mutations in the normal ovary was 0.00% (n=0/7), while the prevalence in benign, borderline and malignant mucinous neoplasms was 57.14% (n=4/7), 90.00% (n=9/10) and 75.61% (n=31/41), respectively. Multiple Kras mutations were detected in 6 cases of mucinous carcinoma, including 5 double mutations with G13D/V14I (n=1), G12V/G13S (n=1), G12D/G13S (n=3) and one triple mutation with A11V/G13N/V14I (n=1). We identified six cases with 3 novel Kras mutations not previously described in the COSMIC database, which included A11V (n=3) and V14I (n=2) in mucinous carcinomas, and A11T (n=1) in a mucinous borderline tumor. In conclusion, Kras mutation appears to be one of the imperative events in the ovarian mucinous adenoma-borderline tumor-carcinoma sequence, as increased numbers of Kras mutations have been shown to be the strongest predictor of unequivocal malignancy in ovarian mucinous neoplasms.